Association Study of DKK2 Polymorphisms with Alcohol Dependence and Alcohol‐Related Harm. (7th October 2013) - Kim, Jason Yongha; Bae, Joon Seol; Park, Byung Lae; Kim, Jeong‐Hyun; Kim, Lyoung Hyo; Kim, Jee Wook; Lee, Boung Chul; Kang, Tae‐Cheon; Choi, Ihn‐Geun; Shin, Hyoung Doo
<x xml:space="preserve">Abstract</x> Background Alcohol dependence (AD) is a common disorder with both environmental and genetic factors. Previous studies have shown that the genomic region from chromosome 4q22‐q32 is closely associated with AD. Furthermore, a study with Irish subjects revealed that the polymorphisms of Dickkopf WNT signaling pathway inhibitor (DKK2), located at 4q25, showed a significant association with AD. Methods We conducted a replication study of the association between DKK2 polymorphisms and AD with 459 alcoholics and 444 normal controls, all of Korean descendent. To rank the AD of the subjects, Alcohol Use Disorders Identification Test (AUDIT) was utilized. Using the TaqMan assay, 21 single‐nucleotide polymorphisms (SNPs) of DKK2 were genotyped. Results Our analysis showed that rs17037102 (Q146R) was significantly associated with overall AUDIT score (p = 0.003, pcorr = 0.05 in dominant model). Further analysis showed that the SNP was significantly associated with alcohol‐related harm (p = 0.001, pcorr = 0.02 in co‐dominant model). Several other SNPs, including the 3 SNPs which were associated with AD in European population, showed marginal associations that were erased when corrections for multiple testing was applied. Furthermore, rs17037102 was in linkage disequilibrium with the nonexonic DKK2 SNPs which showed associations with AD in the previous study with Irish population, which suggests that rs17037102 may be the causal SNP. Conclusions We found 1 DKK2 SNP to be significantly associated with alcohol‐related harm in alcoholic subjects. The SNP might be the causal SNP which led its linked SNPs to show associations in previous studies.